(untitled) (Economic and Political Thought, 2023)
The article refers to general aspects of health policy in North Macedonia after the Macedonian government introduced a package of reforms in recent years to improve the general health of the population. The issues outlined here focus on such aspects of health policy as the implementation of a system of universal health insurance and a new system of primary health care, as well as free health care for children and the elderly, and the expansion of access to preventive and curative services.